PENGOLAHAN MINYAK GORENG BEKAS (JELANTAH) SEBAGAI PENGGANTI BAHAN BAKAR MINYAK TANAH (BIOFUEL) BAGI PEDAGANG GORENGAN DI SEKITAR FMIPAUNNES - Setyaningsih, Natalia Erna; Wiwit, Wasi Sakti (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2017)
Cooking oil is one of the needs of society in order to fulfill daily needs. The economic condition of Indonesian people is very diverse, some use cooking oil for single use but some also use cooking oil for several times usage. The high unsaturated fatty acids in cooking oil, cause cooking oil will be easily damaged in the process of frying (deep frying) because in the process of frying, oil will be heated continuously at high temperatures. The  use  of  used  cooking  oil  or  jelantah  can  cause  adverse  effects  to  the  commu- nity  and  the  environment.  The  adverse  impacts  on  the  community  are  caused  by the  decline  in  the  quality  of  food  fried  with  cooking  oil  which  results  in  disruption  of  public  health.  Adverse  impact  to  the  environment  is  the  disposal  of  cooking   oil   without   first   processing   can   pollute   the   soil   and   water   environment. Utilization of used cooking oil as kerosene replacement fuel is one solution that can be tak- en when facing the bad impact of used cooking oil. In order to serve as a substitute fuel for kerosene, jelantah oil must have karaketristik that is almost the same as kerosene. One of the most important characteristics is the viscosity number. Wrinkled oil has a high viscosity, so that the use of jelantah oil must undergo certain processes to decrease its viscosity. One way to reduce viscosity is by warming at high temperatures over long periods of time. Partners    in    this    devotional    activity    are    the    vendors    of    gorengan    around the  campus  of  UNNES  FMIPA.  They  use  a  lot  of  cooking  oil  in  their  business,  maybe  even  cooking  oil  used  many  times  and  waste  of  used  cooking  oil will   be   thrown   indiscriminately   so   as   to   pollute   the   surrounding   environment. With this devotion is expected the traders gorengan around FMIPA UNNES campus can process waste used cooking oil into fuel substitute kerosene so that will reduce environmental pollution.